Patch-based techniques in medical imaging: 4th International Workshop, Patch-MI 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 20, 2018, proceedings - Bai, Wenjia; Sanroma, Gerard; Wu, Guorong; Munsell, Brent C.; Zhan, Yiqiang; Coupé, Pierrick (Lecture notes in computer science, 2018)
This book constitutes the refereed proceedings of the 4th International Workshop on Patch-Based Techniques in Medical Images, Patch-MI 2018, held in conjunction with MICCAI 2018, in Granada, Spain, in September 2018. The 15 full papers presented were carefully reviewed and selected from 17 submissions. The papers are organized in the following topical sections: Image Denoising¸ Image Registration and Matching, Image Classification and Detection, Brain Image Analysis, and Retinal Image Analysis